Monetary Policy Analysis and Forecasting in the World Economy : A Panel Unobserved Components Approach - Vitek, Francis (IMF Working Papers; Working Paper ;, 2009)
This paper develops a panel unobserved components model of the monetary transmission mechanism in the world economy, disaggregated into its fifteen largest national economies. This structural macroeconometric model features extensive linkages between the real and financial sectors, both within and across economies. A variety of monetary policy analysis and forecasting applications of the estimated model are demonstrated, based on a novel Bayesian framework for conditioning on judgment.